Traumatic Brain Injury in the Elderly is common but is not as Bad as we Think! Exercise, not rest, can ensure faster recovery from post-concussion syndromes "Autobiographical case report" - Suresh Kishanrao (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2021)
Head injuries, medically known as Traumatic Brain Injuries (TBI) are a leading cause of seeking emergency medical care, hospitalization, long hospital stays, disabilities, rehabilitation services, case fatalities and socioeconomic losses in India. Head trauma is one of the common injuries in the old due to trivial falls, and its consequences need not be grievous always. As many of the elderly are on medication for hypertension, diabetes, and heart ailments and due to sudden rising from the bed, or even from the commode or Indian style of squatting plate develop giddiness and fall. Incidence of head injuries is rising all over the world but fortunately more than half of them is either mild or moderate amenable to management with good outcomes. They can sometimes be serious and fatal when left untreated. The epidemiology of TBI is still an enigma in the medical world due to inconsistency in the definition and classification and discrepancies in data collection.  Glasgow Coma Scale (GCS) is a well-accepted tool to assess the seriousness at the first visit to stratify, monitor the prognosis, and recovery of brain functions in patients with traumatic brain injury. Seniors over the age of 60 years with head injury are generally considered to have a poor outcome. However, a recent large multicentric China epidemiologic study of minor head injury patients (GCS 13-15) reported over 90 % survival, few with minor consequences. Another large-scale retrospective study at a level II trauma centre in Florida from 2005 to 2008, too indicated that the outcome of elderly over 65 years old had a survival rate of over 80 %. I report my own autobiographical case of a closed head injury, with good outcome due to timely care and early initiation of aerobic exercise (waking & tread meal) for recovery from concussion injury due to fall in washroom, with no major post-concussive symptoms.